The integration of TRIZ methods with eco-design and lean design: a literature review and future research directions to the development of a new model. - Muiambo, Cláudia (2019)
This work presents a review of the literature on TRIZ methods and tools applied to eco-design and to lean design to support designers and engineers in the development of innovative sustainable product and pro- cesses. A review of existing scientific work on those subjects has the potential to guide scholars by provid- ing examples, ideas, information and insight to the field problems and to the existing links. The specific methodology to use in this literature review starts with the formulation of the research questions to guide the review by identifying the findings of the relevant individual studies addressing the research questions specifically establishing to what extent the existing research concerning Eco-design initiatives and Lean design initiatives has progressed towards the use of TRIZ methods over the last two decades and describe directions for further research concerning the use of TRIZ in eco-design and lean design paradigms. The proposed framework including the main Eco and Lean design tools and key performance indicators usually used in Eco and Lean paradigms is presented and will be used in future work to better identify the possible gaps, issues and opportunities for further research concerning the development of a new model to integrate TRIZ with ECO-LEAN design.